The APPLICATION OF THE TGT (TEAMS GAMES TOURNAMENT) METHOD AS AN INNOVATIVE APPROACH IN TEACHING SIMPLE PRESENT TENSES: A Descriptive Study on the Application of TGT in Teaching Grammar - El-Sulukiyyah, Ana Ahsana; Khariroh; Rizanita, Melisa (The Journal Of English Teaching For Young And Adult Learners, 2025)
This study explores the implementation and effectiveness of the Teams Games Tournament (TGT) method in students’ understanding of the Simple Present Tense. Conducted as a qualitative case study in a 10th-grade English class at MAN Kota Pasuruan, Indonesia, this study aims to address challenges often associated with grammar teaching, such as low student motivation and engagement. Data collection involved classroom observations and written tests with students to gain qualitative insights into learning and outcomes. The results showed that the TGT method significantly on students’ understanding of the Simple Present Tense by providing a structured yet enjoyable learning experience. Group discussions encouraged collaboration, while the competitive element of TGT encouraged active participation and sustained interest in the material. In addition, the method contributed to the development of students’ social skills, such as teamwork, communication, and respect for peers’ contributions, thus creating a supportive and interactive classroom environment.